2015
DOI: 10.1007/s12010-015-1733-9
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of an Antibacterial Compound, 2-Hydroxyl Indole-3-Propanamide, Produced by Lactic Acid Bacteria Isolated from Fermented Batter

Abstract: Lactic acid bacteria are known to produce numerous antimicrobial compounds that are active against various pathogens. Here, we have purified and characterized a novel low-molecular-weight (LMW) antimicrobial compound produced by Lactobacillus and Pediococcus isolated from fermented idly and uttapam batter. The LMW compound was extracted from cell-free supernatant using ice-cold acetone, purified by gel permeation and hydrophobic interaction chromatography. It exhibited antimicrobial activity against Gram-posit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 28 publications
1
6
0
Order By: Relevance
“…The inhibitory spectrum of compounds in the fractions AI and AII produced by L. lactis ID1.5 is presented in 4). Recently, low molecular weight compound produced by Lactobacillus and Pediococcus has been described as antimicrobial against Gram-positive and Gram-negative bacteria (Jeevaratnam et al 2015). Interestingly, in our work the compound AI showed antimicrobial activity against all L. lactis strains tested (Table 4).…”
Section: Determination Of Inhibitory Spectrumsupporting
confidence: 55%
“…The inhibitory spectrum of compounds in the fractions AI and AII produced by L. lactis ID1.5 is presented in 4). Recently, low molecular weight compound produced by Lactobacillus and Pediococcus has been described as antimicrobial against Gram-positive and Gram-negative bacteria (Jeevaratnam et al 2015). Interestingly, in our work the compound AI showed antimicrobial activity against all L. lactis strains tested (Table 4).…”
Section: Determination Of Inhibitory Spectrumsupporting
confidence: 55%
“…isolated from dosa batter was beneficial in their selection for future food and feed applications [15]. The chemical compound (2-hydroxyl indole-3-propanamide) derived from LAB strains isolated from idly and uttapam batter has potential antibiotic properties that protect probiotic bacteria against the pathogenic strains [16]. With this background, the study objectives are to isolate LAB from dosa batter that has probiotic potential and study its inhibitory potential against the carbohydrate hydrolyzing enzymes (α-glucosidase and α-amylase).…”
Section: Introductionmentioning
confidence: 99%
“…Another novel LMW compound was obtained from Lactiplantibacillus plantarum KJB23 studied by our group which was found to be resistant to acid protease (Kavitha et al 2020). Previous studies reported other antimicrobial LMW compounds, such as phenyl lactic acids and 2-Hydroxyl Indole-3-Propanamide, produced by Lactiplantibacillus plantarum (Yang et al 1997;Schwenninger et al 2008;Jeevaratnam et al 2015).…”
Section: Discussionmentioning
confidence: 99%